Critique of a Language-Learning Website - Soh, Or Kan (2011)
Listening plays a crucial part in the learning of overseas students in the United Kingdom. Students can never follow a lecture or discussion in English without listening. Traditional classroom teaching in listening limits students’ time and space. However, the Web-based listening course accommodates listeners a great deal, enabling them to access the Internet at their own pace. In this paper, the author would like to study on a language learning Website for developing learners’ listening skills, designed by the CELE (Centre for English Language Education) at the University of Nottingham. In the first part, the author will review the issues concerning listening, conventional materials design, CALL (computer assisted language learning) and actual Websites established for EAP (English academic purposes). Through analysis, the author would develop a set of evaluation criteria in order to evaluate the CELE listening Website. These guidelines should also be helpful for teachers and students to select suitable online listening materials. By using these criteria and comparing with other Websites for similar purposes, the author would highlight the strengths and weaknesses of the CELE Website and offer suggestions for its improvement. In the last section, the author would consider the generalisability of the Website in respect of design principles, exercise types and tools, to check whether it is appropriate for teaching listening in a specific context and whether it is applicable for creating a parallel site developing reading skills. Keywords: listening skills, English academic purposes, computer-assisted language learning, reading skills